FRICTIONLESS, FUN, AND FAST: PATHWAYS TO SPONTANEOUS BUYING IN DIGITAL PAYMENTS - GRACELA MARISA SANAPANG; Sanny Suliantoro; Levani Chandra; Leony Theresia Talaran; Steven Yoel Jonathan; Anthony Patrick Tjandani (Universitas Pelita Harapan, 2026)
This study examines the effect of digital convenience on impulsive buying behavior, with perceived usefulness and hedonic motivation as mediating variables among e-wallet users in Indonesia. A quantitative explanatory research design was employed, with data collected from 157 respondents through purposive sampling using an online questionnaire. Structural Equation Modeling (SEM-PLS) was applied to analyze the relationships between variables. The results indicate that digital convenience does not have a direct effect on impulsive buying, but it significantly influences impulsive buying indirectly through both perceived usefulness and hedonic motivation. Hedonic motivation was found to be the stronger mediator, suggesting that emotional enjoyment plays a more dominant role than cognitive perceptions of usefulness in driving impulsive purchases. These findings highlight the importance of enhancing both functional convenience and hedonic experiences in digital platforms to better understand consumer behavior in the Indonesian e-commerce context.